P08.23 Sero-epidemiological assessment indicates high prevalence of c. trachomatis in samoan women with infertility. (13th September 2015) - Menon, S; Stansfield, S; Walsh, M; Hope, E; Isaia, L; Righarts, A; Niupulusu, T; Temese, SVA; Iosefa, L; Auvaa, L; Tapelu, S; Motu, MF; et al.
Abstract : Introduction: Chlamydia trachomatis (CT) is one of the most common bacterial sexually transmitted infections in the world. Due to the asymptomatic nature of the disease, the infection is frequently undiagnosed resulting in the development of serious sequelae such as pelvic inflammatory disease, ectopic pregnancy and tubal infertility in women. The prevalence of CT infection in Samoa was previously estimated to be 30.9%, based on pregnant women attending antenatal clinics. The high prevalence of CT infection may imply a high probability of increased risk of sequelae such as infertility in Samoan women. Methods: Serological prediction of CT infertility as indicated by titers of serum antibodies to CT in infertile women was conducted using a series of commercial tests such as MEDAC and ANilabsystems serology kits. The correlation between self-reported infertility and epidemiological factors to serologically predicted CT infertility was determined. Self reported infertility in women was defined based on their patient history as the inability to get pregnant after trying for more than 1 year. Results: Women who self-reported infertility had a high prevalence of serologically predicted chlamydial infertility (36%), which was significantly different from fertile women (18%). The study accounted for confounders using stepwise multiple logistic regression analysis (BMI, number of cigarettes per day, age). MEDAC CT IgG p-ELISA correlated with self-reported infertility (OR 2.32, 94% CI 1.25–4.33; P = 0.01), while Anilabsystems CT IgG ELISA correlated with the current infections diagnosed by PCR (OR 1.93, 95% CI 1.11–3.37; P = 0.02). Conclusion: The study highlights the importance of serological tests in potentially identifying women with CT-related infertility. The high prevalence of CT and women testing positive in CT infertility tests suggests that CT could be a major contributory factor to infertility, and a major unrecognised disease burden in the Samoan population. Disclosure of interest statement: No conflicts of interest.